Operational Risk Assessment (ORA) for Local Government Engineering Department (LGED) in Bangladesh : Final Report, Volume 1 - World Bank (Washington, DC, 2013)
The Local Government Division, Ministry of Local Government, Rural Development and Cooperatives (LGD) agreed, as part of the identification of a follow-up project to the on-going Rural Transport Improvement Program (RTIP), to launch an Operational Risk Assessment (ORA) of the Local Government Engineering Department (LGED). The ORA draws on and adapts previous work to develop methodologies to assess and suggest mitigation measures for fiduciary risks, as well as inherent risks linked with road and infrastructure construction and maintenance, administrative control risks, and risks associated with political influence. The Fiduciary and Operational Risk Management Improvement Plan (FORMIP) built on the first report to: (i) assess fiduciary and operational risks in LGED's management of projects, assets and other resources, and in LGD's oversight function, that are likely to be major factors in possible funds leakages, delays and undue interferences and overall inefficient use of public resources; (ii) prioritize options which are realistic and available to effectively minimize (and where possible, eliminate) the major operational risks identified; and (iii) identify options for mechanisms which (drawing on this ORA as a 'baseline') will facilitate efficient future monitoring of operational risks in LGED and the LGD. An important conclusion of the ORA is that most of the recommended actions are within LGED's authority to take, with support from development partners and routine budgetary spending and staffing authorizations from other agencies. However, the action plan proposed in the report will be greatly enhanced if supported by further development of the Government's, Bank's and development partners' programs to improve governance and reduce overall operational risk in Bangladesh. Individual sub-sector reports such as these ORA can only have a limited impact in the absence of wider and widely supported programs.